2015
DOI: 10.1002/dvg.22879
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Evc2/Limbin global and conditional KO mice and its roles during mineralized tissue formation

Abstract: Summary Ellis-van Creveld (EvC) syndrome (OMIM 225500) is an autosomal recessive disease characterized with chondrodysplastic dwarfism in association with abnormalities in oral cavity. Ciliary proteins EVC and EVC2 have been identified as causative genes and they play an important role on Hedgehog signal transduction. We have also identified a causative gene LIMBIN for bovine chondrodysplastic dwarfism (bcd) that is later identified as the bovine ortholog of EVC2. Here, we report generation of conventional and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(65 citation statements)
references
References 34 publications
7
58
0
Order By: Relevance
“…The same group also demonstrated compromised bone collar formation in Evc −/− mice in the C57BL/6 homogenous background but showed that both proliferation and differentiation of chondrocytes are compromised in mutant mice (Pacheco et al 2012). EVC and EVC2 are mutually required for their ciliary localization and loss of Evc2/Limbin results in similar skeletal phenotypes found in Evc −/− mice (Caparrós-Martín et al 2013;Zhang et al 2015).…”
Section: Primary Ciliamentioning
confidence: 82%
“…The same group also demonstrated compromised bone collar formation in Evc −/− mice in the C57BL/6 homogenous background but showed that both proliferation and differentiation of chondrocytes are compromised in mutant mice (Pacheco et al 2012). EVC and EVC2 are mutually required for their ciliary localization and loss of Evc2/Limbin results in similar skeletal phenotypes found in Evc −/− mice (Caparrós-Martín et al 2013;Zhang et al 2015).…”
Section: Primary Ciliamentioning
confidence: 82%
“…Upon induction of Hedgehog signaling, the EVC/EVC2 complex interacts with SMO at the base of cilium, which affects GLI2 accumulation in the ciliary tips [21, 23]. Consistent with in vitro mechanistic studies, diminished Hedgehog signaling was observed in the growth plates of mice lacking either Evc or Evc2 [23, 26, 27]. Since the Hedgehog-PTHrP loop has a central role in regulating chondrocyte proliferation and maturation, thereby determining the length of the appendicular skeleton, disrupted Hedgehog signaling in the growth plate is the speculated reason for dwarfism in the EvC syndrome [21, 23].…”
Section: Introductionmentioning
confidence: 95%
“…This discrepancy between the function of EVC/EVC2 in transducing Hedgehog signaling and phenotypic observations in Evc or Evc2 mutant mice prompted us to ask to what extent does the loss of function of Evc/Evc2 reduce Hedgehog signaling, and why does Evc/Evc2 loss of function specifically impact limb development. To answer these questions, we investigated Hedgehog signaling and FGF signaling levels during defective endochondral ossification in Evc2 mutant mouse lines [27]. We demonstrate that a nonsense mutation in Evc2 that mimics mutations seen in EvC patients, leads to compromised but not abrogated Hedgehog signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Schema of main compartments of the primary cilium and gene product localization with association to dental phenotype. Beales et al 1999 Waters andBeales 2011 (continued) less severe phenotypes in the incisors and molar teeth (Zhang et al 2015). These data suggest that the primary cilia residing in the neural crest-derived mesenchyme are necessary for normal mineralization of the tooth.…”
Section: Ciliopathy Syndromes With Dental Phenotypementioning
confidence: 90%